(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2017)
The Director of Mayéutica Revista Científica de Humanidades y Artes, Francisco Camacho, received Honorable Mention in the XX Contest of Monographs of the Latin American Center for Administration for Development (CLAD), which in 2017 had the theme of integrity and ethics in the public function . Camacho, who participated with 11 other researchers from Latin America, the Caribbean, Spain and Portugal to whom their manuscripts were admitted, presented an essay entitled "Justice, democracy and capacities: ethical reflections on good governance from the perspective of human development "And he was the only Venezuelan who presented a text for the evaluation of CLAD. The winner of the First Prize of the Contest was the Costa Rican Rafael León Hernández, while the Chilean Nicolás Lago Machuca and the Spanish Goizider Manotas Rueda won the Second and Third Prizes, respectively.